Detection of risk for depression among adolescents in diverse global settings: protocol for the IDEA qualitative study in Brazil, Nepal, Nigeria and the UK - Christian Kieling; Brandon A Kohrt; Syed Shabab Wahid; Gloria A. Pedersen; Katherine Ottman; Abigail Burgess; Kamal Gautam; Thais Martini; Anna Viduani; Olufisayo Momodu; Crystal Lam; Helen L. Fisher; et al. (BMJ Open)
Introduction Globally, depression is a leading cause of disability among adolescents, and suicide rates are increasing among youth. Treatment alone is insufficient to address the issue. Early identification and prevention efforts are necessary to reduce morbidity and mortality. The Identifying Depression Early in Adolescence (IDEA) consortium is developing risk detection strategies that incorporate biological, psychological and social factors that can be evaluated in diverse global populations. In addition to epidemiological and neuroscience research, the IDEA consortium is conducting a qualitative study to explore three domains of inquiry: (1) cultural heterogeneity of biopsychosocial risk factors and lived experience of adolescent depression in low-income and middle-income countries (LMIC); (2) the feasibility, acceptability and ethics of a risk calculator tool for adolescent depression that can be used in LMIC and high-income countries and (3) capacity for biological research into biomarkers for depression risk among adolescents in LMIC. This is a multisite qualitative study being conducted in Brazil, Nepal, Nigeria and the UK.Methods and analysis A systematic set of qualitative methods will be used in this study. The Delphi method, Theory of Change (ToC) workshops, key-informant interviews and focus group discussions will be used to elicit perspectives on the study topics from a broad range of stakeholders (adolescents, parents, policy-makers, teachers, health service providers, social workers and experts). Delphi panellists will participate in three survey rounds to generate consensus through facilitated feedback. Stakeholders will create ToC models via facilitated workshops in the LMIC sites. The framework approach will be used to analyse data from the study.Ethics and dissemination Ethical approvals were received from the Ethics Review Board of George Washington University and from site-specific institutions in Brazil, Nepal, Nigeria and the UK. The findings generated from this study will be reported in highly accessed, peer-reviewed, scientific and health policy journals.